Effect of convergent–divergent flow on thermal and crystallization properties of PP/MWCNTs nanocomposites. Issue 31 (8th May 2015) - Yin, Xiaochun; Yu, Zhongwei; Zhang, Guizhen; Yang, Zhitao; Xu, Baiping
ABSTRACT A melt‐mixing process based on convergent–divergent flow has been used to prepare PP/MWCNT composites with a self‐built convergent–divergent die (C‐D die) composed of different numbers of convergent plates. Dynamic extensional deformation was generated in the C‐D die, which improved the mixing effect and mixing efficiency of the composites during extrusion. The C‐D die acted as a mixer for composites when mounted onto a capillary rheometer. The residence time of PP/MWCNTs melt in the extensional flow field is adjusted by changing the numbers of convergent plates and the velocity of the ram. The intensity of extensional flow field is controlled by the structure of the convergent plate and the ram velocity. Influences of convergent–divergent flow on PP/MWCNTs composites were characterized in terms of transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). TEM results showed that MWCNTs disperse more homogeneously with the increase of convergent plates. DSC showed that the crystallinity of PP/MWCNTs composites increased and the crystallization temperature shifted to higher temperature with the increase of the numbers of the convergent plates. TGA showed that the thermal stability of composites improved remarkably. The decomposition temperature increases from 381 to 408.2°C when the numbers of convergent plates increased from 2 to 8. In addition, the increase of ram velocity also has the same influences on the dispersion of MWCNTs in the resin and the properties of PP/MWCNTs nanocomposites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42330.